Biologic width changes around loaded implants inserted in different levels in relation to crestal bone: histometric evaluation in canine mandible - Farias Pontes, Ana Emilia; Ribeiro, Fernando Salimon; Iezzi, Giovanna; Piattelli, Adriano; Cirelli, Joni Augusto [UNESP]; Marcantonio, Elcio [UNESP] (Blackwell Publishing, 2008)
Objectives: The aim of the present study was to evaluate histometric changes around dental implants inserted at different levels in relation to the crestal bone, under different loading conditions.Material and methods: Thirty-six implants were inserted in the edentulous mandible of six mongrel dogs. Each implant was assigned to an experimental group according to the distance from the top of the implant to the crestal bone: Bone Level (at the crestal bone level), Minus 1 (1 mm below the crestal bone) or Minus 2 group (2 mm below the crestal bone). Each hemimandible was submitted to a loading protocol: conventional or immediate restoration. After 90 days, the animals were killed. Specimens were processed, and measurements were performed concerning the length of soft and hard peri-implant tissues. Data were analyzed using ANOVA and Student's t test (alpha=5%).Results: Among conventionally restored sites, the distance from the most coronal position of soft tissue margin (PSTM) and first bone-implant contact (fBIC) was greater for Minus 2 than for Bone Level and Minus 1 sites (P=0.03), but significant differences were not observed among immediately restored sites. Differences among groups were not observed concerning the PSTM, and the distance from the implant-abutment junction to fBIC. Greater amounts of lateral bone loss were observed for conventionally than for immediately restored sites (P=0.006).Conclusions: These findings suggest that the apical positioning of the top of the implant may not jeopardize the position of soft peri-implant tissues, and that immediate restoration can be beneficial to minimize lateral bone loss. Further studies are suggested to evaluate the clinical significance of these results in longer healing periods.
Keywords: animal experiments; bone-implant interactions; morphometric analysis; periodontology; prosthodontics; soft tissue-implant interactions; statistics; wound healing